Impaired postprandial response of the insulin‐like growth factor system in maintenance haemodialysis. (19th November 2013) - Reinhard, Mark; Frystyk, Jan; Jespersen, Bente; Randers, Else; Bjerre, Mette; Christiansen, Jens S.; Flyvbjerg, Allan; Bibby, Bo M.; Ivarsen, Per
Summary Objective Patients on maintenance haemodialysis (HD) have reduced circulating free and bioactive insulin‐like growth factor I (IGF‐I) due to increased IGF‐binding proteins (IGFBPs). This study investigated the postprandial response of the IGF system in HD patients compared with matched healthy subjects. Design and Patients In a crossover study, twelve nondiabetic HD patients were assigned in a random order to three 10‐h study days: (1) a non‐HD day with one meal served at baseline (NHDM1), (2) an HD day with one meal served during HD (HDM1) and (3) an HD day with two meals served during and after HD, respectively (HDM2). Twelve healthy controls conducted session 1. Results After the baseline meal, insulin concentrations changed similarly in HD patients and controls, whereas hyperglycaemia was more prolonged in HD patients (P < 0·001). Postprandial IGFBP‐1 showed greater reductions from baseline in controls (−76% [−81; −70%], mean [95% confidence intervals], P < 0·001) than in patients on non‐HD days (−45% [−57; −30%], P < 0·001). In the latter group, the response was even more attenuated during HD (−22% [−38; −1%] and −24% [−40; −4%], P ≤ 0·041). After the second meal on HDM2 days, IGFBP‐1 further decreased (−50% [−61; −37%], P < 0·001), whereas IGFBP‐1 returned to baseline levels on the other study days. Consistently, at the end of the study days, bioactive IGF‐I was significantly above baseline only on HDM2 days (+22% [+5; +43%], P = 0·012). Conclusions HD patients were unable to suppress IGFBP‐1 to the same extent as healthy controls, which may increase the risk of protein–energy wasting in maintenance HD. A second meal after HD, however, effectively suppressed IGFBP‐1 and increased bioactive IGF‐I.